2019
DOI: 10.1007/978-3-030-04031-4_28
|View full text |Cite
|
Sign up to set email alerts
|

Lesson Study in Mathematics Initial Teacher Education in England

Abstract: Drawing on research in mathematics initial teacher education (ITE) in England, this chapter explores the potential of lesson study to support pre-service mathematics teachers' pedagogical development. We draw attention to ways in which lesson study can be highly transformative of beginning mathematics teachers' pedagogical learning. We consider the current ITE context in England and analyse potential opportunities and challenges for incorporating lesson study into mathematics ITE courses. We conclude by propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In England, pre-service teachers who participate in lesson study typically do so in schools where they undertake their teaching placements but at the instigation of the HEI (Higher Education Institution). Several different models of lesson study have been adopted in ITE courses in England in recent years (Baldry & Foster, 2019). The composition of the lesson-study team varies, with almost all combinations of university tutors, pre-service teachers and school-based mentors seen somewhere.…”
Section: Lesson Study Within Ite Partnershipsmentioning
confidence: 99%
See 2 more Smart Citations
“…In England, pre-service teachers who participate in lesson study typically do so in schools where they undertake their teaching placements but at the instigation of the HEI (Higher Education Institution). Several different models of lesson study have been adopted in ITE courses in England in recent years (Baldry & Foster, 2019). The composition of the lesson-study team varies, with almost all combinations of university tutors, pre-service teachers and school-based mentors seen somewhere.…”
Section: Lesson Study Within Ite Partnershipsmentioning
confidence: 99%
“…A common feature across different models of lesson study is a cycle beginning with collaborative planning, followed by an observed research lesson and some form of post-lesson review. We have previously outlined a 5-step approach to lesson study, which we have found effective and achievable in supporting pre-service teachers' first experiences of lesson study (Baldry & Foster, 2019; see Figure 2). We have argued that this structure can maximise the chances of a positive first experience of lesson study that may encourage pre-service teachers and schools to persevere with the approach.…”
Section: Lesson Study Within Ite Partnershipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesson study is a powerful form of professional development, which enables Japanese teachers to improve their lessons and enhance their teaching competence (Fernandez and Yoshida 2012). In recent years, many other countries have sought to adopt and adapt aspects of lesson study for use in their own schools, especially in mathematics (Baldry and Foster 2019;Lewis 2002;Stigler and Hiebert 1999;Takahashi and McDougal 2016;Takahashi and Yoshida 2004;Yoshida 1999). However, for Japanese teachers, lesson study is so familiar that it is "like air" (Fujii 2014, p. 80), meaning that essential aspects of the process may be taken for granted and not critically interrogated.…”
Section: Introductionmentioning
confidence: 99%
“…In countries where lesson study is not yet firmly embedded in school culture, the importance of the role of the koshi may well be acknowledged, but those taking on this role may lack confidence in providing final comments in research lessons and may wonder what kinds of comments may be most helpful for the participants (e.g., Baldry and Foster 2019). Even in Japan, a new koshi will not yet have gained the experience that makes this process feel natural, and the quality of final comments is likely to be improved by giving attention to the final comments made by more experienced koshis.…”
Section: Introductionmentioning
confidence: 99%